Enhancement of the Protective Activity of Vanillic Acid against Tetrachloro-Carbon (CCl4) Hepatotoxicity in Male Rats by the Synthesis of Silver Nanoparticles (AgNPs) - Eman S. Alamri; Haddad A. El Rabey; Othman R. Alzahrani; Fahad M. Almutairi; Eman S. Attia; Hala M. Bayomy; Renad A. Albalwi; Samar M. Rezk (Molecules, 2022)
In the current study, the hepatoprotective activity of vanillic acid, silymarin, and vanillic acid-loaded silver nanoparticles (AgNPs) against CCl4-induced hepatotoxicity was tested in male rats for four weeks. Thirty male rats were divided into five groups (n = 6). The 1st group was a negative control, the 2nd group was a positive control, the 3rd group was treated with 100 mg/kg b.w. of vanillic acid, the 4th group was treated with 100 mg/kg b.w. of vanillic acid–AgNPs, and the 5th group was treated with 50 mg/kg b.w. of silymarin. The CCl4-induced hepatic toxicity in the 2nd group was revealed by the liver function and all other biochemical tests. Liver enzymes, bilirubin, lipid peroxidation, lactate dehydrogenase, and interleukin-6 were elevated, whereas, total protein, antioxidant enzymes, and irisin were decreased compared to the negative control. The hepatic tissues were also injured as a result of the CCl4-induced hepatotoxicity. Treating the hepatotoxic rats with vanillic acid moderately protected the rats of the 3rd group, whereas treatment with vanillic AgNPs and silymarin in G4 and G5, respectively, greatly protected the rats against the CCl4 hepatotoxicity, approaching the normal biochemical levels and liver tissue appearance. The biochemical tests were confirmed by the histological investigations of liver tissue.